Impact of pasteurization method and fat on milk: Relationships among rheological, tribological, and astringency behaviors. (March 2018) - Li, Y.; Joyner (Melito), H.S.; Lee, A.P.; Drake, M.A.
Abstract: It is commonly stated that ultrapasteurized (UP) milk is more astringent than high-temperature short time (HTST) pasteurized milk but studies on this topic are limited. This study's objective was to determine impacts of pasteurization method, storage time, and fat content on relationships among bovine milk astringency, rheological, and tribological behaviors. Skim, 1% fat, and whole milk were pasteurized by direct UP, indirect UP, or HTST pasteurization. Milk sensory astringency and mechanical friction and viscosity were determined at 1, 4, and 8 weeks post-processing. Increased fat content increased viscosity but decreased friction coefficients. Increased storage time did not significantly affect viscosity or friction coefficients. UP milk was generally more astringent than HTST-pasteurized milk. Saliva addition (3%, v/v) did not impact instrumental friction. No direct relationships were found among astringency, viscosity, and friction behavior. Overall, UP did not significantly impact milk viscosity and astringency; the astringency mechanism was not saliva-mediated.